How authentic leadership promotes individual creativity: the mediating role of affective commitment - Ribeiro, N.; Duarte, A. P.; Filipe, R.; Oliveira, R. T. (Journal of Leadership and Organizational Studies, 2019)
This study sought to provide a more comprehensive understanding of how authentic leadership can affect employees’ individual creativity through affective commitment’s mediating role. The sample included 177 leader–follower dyads from 26 private, small- and medium-sized enterprises. Followers reported their levels of affective commitment and perceptions of authentic leadership, and leaders assessed each follower’s level of creativity. The results show that authentic leadership has a positive impact on affective commitment and creativity. Moreover, affective commitment fully mediates the relationship between perceived authentic leadership and individual creativity. Organizations can thus increase employees’ affective commitment and creativity by encouraging their managers to adopt more authentic leadership styles. Additional studies with larger samples are needed to determine more clearly not only authentic leadership’s influence on individual creativity but also other psychosocial and personal variables’ effects on that relationship.